Test Of The Accuracy Of The Qibla Direction Of The Graves Of Hubbal Khaer Hall, Eyat Mayang Village Usingmizwala Qibla Finder - Wahyudi, Imam (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research is grounded in academic concern arising from the Researcher’s observations regarding the qibla direction of graves in Hubbal Khaer Hamlet, Eyat Mayang Village, which are not aligned with one another. Therefore, the objectives of this study are to determine the community’s understanding of how to determine the qibla direction of graves, to identify the methods used by the people of Hubbal Khaer Hamlet in determining the qibla direction, and to assess the accuracy of the qibla orientation of graves in the area.This study employs a field research design with a qualitative approach. The qualitative approach is used to reveal the facts occurring in the field related to the Accuracy Test of the Qibla Direction of Graves in Hubbal Khaer Hamlet, Eyat Mayang Village.The findings of this research show that the determination of the qibla direction of graves in Hubbal Khaer Hamlet is carried out using the method of observing the direction of the sunset, as the community in earlier times was not yet familiar with modern or advanced instruments. Another method used is relying on the opinions of religious scholars or Tuan Guru. In addition, the community also follows the orientation of previously established graves. The accuracy test conducted using the Mizwala Qibla Finder indicates that several grave orientations are inaccurately aligned. The lower graveyard shows a deviation of 45° toward the south, indicating that its qibla direction is inaccurate. Meanwhile, the upper graveyard shows a deviation of approximately 4° toward the north, indicating that its qibla direction is less accurate.